A3 thinking approach to support lean product and process development - Mohd Saad, Norhairin (Cranfield University, 2013)
This research project aims to develop a novel A3 thinking approach to support knowledge driven design that aids the generation of decision making within a Lean Product and Process Development (LeanPPD) environment. This research comprises the development of a new A3 template as a technique of problem solving in product design, the adoption of a reflection practice structured in a new A3 template for knowledge capture and sharing, and the generation of the process of using the A3 thinking approach for effective implementation. Providing useful knowledge as a design reference to generate decision making at the initial stages of product development in product design helps the designers to prevent recurrence of the same problem, eliminate design mistakes and enhance design decision. In order to achieve a novel A3 thinking approach, a research methodology consisting of four phases was developed. The first phase synthesises the A3 best practice through literature and documentation reviews. The gap analysis and results from the reviews have identified several problem-solving approaches and learning cycles that have to be considered in the research. The second phase is to evaluate the approaches and their impacts and applications in product design. In order to complete this, several research methods are selected and performed (e.g. focus group and semistructured interview) within the collaborative companies. The third phase is to develop the A3 thinking approach by utilising the LAMDA learning cycle, developing a new A3 template or so-called A3LAMDA, adopting the reflection practice and generating the process of using the new A3 thinking approach. Finally, the validation of the new A3 thinking approach through industrial case studies and expert judgements have been performed. This approach has been implemented in the automotive sector and was applied to four industrial case studies and six A3LAMDA reports were collected. As a result of the findings of this research, the utilisation of the A3 thinking approach aided the generation of knowledge driven design in product design by integrating the knowledge management capabilities; knowledge creation, capture and sharing.
Keywords: A3 thinking; A3LAMDA; lean thinking; lean design; design problem solving; knowledge driven design